Mental health experiences of African, Caribbean and Black (ACB) mothers living with HIV in the context of infant feeding - Josephine Etowa; Edidiong Ekanem; Oluwakemi Ariyo; Haoua Inoua; Yvette Ashiri; Hilary Nare; Eno Akan Essien; Egbe B. Etowa (Elsevier, 2021)
Background: The stressful duality of motherhood while living with HIV is often further compounded by inflexible infant feeding regimes in diasporic settings. National infant feeding guidelines for mothers living with HIV (LWH) are based on World Health Organization (WHO) recommendations, which differ between low- and middle- vs. high-income countries and are more likely to contradict the cultural norms of sub-Saharan African communities. African, Caribbean, and Black mothers living with HIV (ACB- mothers LWH) often grapple with personal preferences and cultural norms vs. national guidelines for infant feeding, which often creates great tension at the intersection of these contradicting feeding protocols, subsequently leading to stressful motherhood experiences in the context of HIV. Purpose: The paper describes the mental health concerns and coping strategies of ACB mothers living with HIV in the context of infant feeding amidst contradicting cultural expectations and guideline. Methods: This is a qualitative study drawn from a broader community-based participatory research (CBPR) Focused ethnography (FE) was used to understand infant feeding-related stressors and coping strategies of ACB- mothers living with HIV. In-depth interviews of 61 ACB-mothers living with HIV were conducted, transcribed verbatim, and thematically analyzed. An audit trail, peer/team debriefing, and member checking ensured data credibility. Findings: Common stressors included cultural pressure toward certain feeding choices, fear of infecting the baby, and fear of inadvertent HIV disclosure and stigma; all of which could culminate in mental health crises if not properly managed. Coping strategies were deliberate effort to keep fit physically and mentally. Discussion and implication: Cultural expectations of "good motherhood" play a strong role in how ACB women judge their own motherhood efforts. Thus, alignment of policies to cultural expectations is key to mitigating psychosocial distress and resultant mental health problems. Conclusion: Mental distress experienced by ACB- mothers living with HIV around infant feeding choices may negatively affect their well-being and consequently their ability to care for their infants. A combination of culturally responsive guidelines, provision of social and community support, and educational efforts is necessary to reduce the mental health burden on ACB- mothers living with HIV.